The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/biof.1538
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of curcumin on prevention of drug‐induced nephrotoxicity: A review of animal studies

Abstract: Drug‐induced nephrotoxicity is a frequent serious adverse effect, contributing to morbidity and increased healthcare utilization. Prevention or reversal is key. Curcumin has useful biological features that include antioxidant, anti‐inflammatory, and anticancer properties. This review covers aspects of curcumin in relation to prevention of drug‐induced nephrotoxicity: dosage and schedule, effect on kidney biomarkers and histological changes, and mechanisms of curcumin's protective effects. Despite success in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Over 100 in vitro and animal studies show that curcumin ameliorates many causes of kidney damage ( Supplementary data, Fig. S1 depicts curcumin's effects relevant to CKD) [ 9–11 ], and some small clinical trials suggest curcumin reduces albuminuria in patients with CKD ( Supplementary data, Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 in vitro and animal studies show that curcumin ameliorates many causes of kidney damage ( Supplementary data, Fig. S1 depicts curcumin's effects relevant to CKD) [ 9–11 ], and some small clinical trials suggest curcumin reduces albuminuria in patients with CKD ( Supplementary data, Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…master regulator of antioxidant response nuclear factor erythroid-derived 2 (Nrf2) induction, mitochondrial dysfunction inhibition, inflammatory response amelioration, antioxidant enzymes preservation, and oxidative stress prevention. 44 Curcumin was effective in the prevention of an increase in serum levels of urea, creatinine, and MDA, compared with the control group. In a study by Mercantepe et al, the effects of curcumin in cisplatininduced nephrotoxicity in rats was evaluated.…”
Section: Discussionmentioning
confidence: 93%
“…Given the problems mentioned above, many researchers have tried solving the problems in nephrotoxicity caused by NSAIDs by using compound preparations (İlbey et al., 2009 ; Ortiz et al., 2010 ; Gao et al., 2019 ; Motaharinia et al., 2019 ); it was demonstrated that the extracts of Phyllanthus amarus Sch, umach. & Thonn (Adeneye & Benebo, 2008 ), Trifolium repens leaf extract (Ahmad & Zeb, 2020 ), and Salacia oblonga (Palani et al., 2011 ), when combined with NSAIDs, can exert their unique pharmacological effects as well as protect the kidney.…”
Section: Introductionmentioning
confidence: 99%